Perancangan Trainer KIT Mixing Liquid Machine Berbasis PLC dan HMI sebagai Media Pembelajaran Sistem Kendali Industri di SMK Negeri 1 Padang - Novita Sari Nur Saputri; Winda Agustiarmi; Almasri; Rido Putra (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to design and develop a mixing liquid machine trainer kit based on a Programmable Logic Controller (PLC) and Human Machine Interface (HMI) as a learning medium for the Industrial Control Systems course at SMK Negeri 1 Padang. The background of this research is the limited availability of practical learning media in the laboratory, which is still simple and not yet integrated with industrial automation systems required by the workforce, resulting in a lack of students’ hands-on experience in operating industrial control systems. This research employed a Research and Development (R&D) method using a development model consisting of needs analysis, design, development, validation, and practicality testing stages. The resulting product is a trainer kit that simulates a two-liquid mixing process using an automatic control system based on the Omron CP1E E40SDR-A PLC and process visualization through an EasyBuilder Pro-based HMI. The results show that the developed product has a very high level of validity based on expert evaluations in both material and media aspects, and it also demonstrates a high level of practicality based on student trials. This indicates that the developed trainer kit is feasible and effective as a learning medium to improve students’ conceptual understanding and practical skills in industrial control systems. Therefore, this trainer kit is expected to bridge the competency gap between vocational school graduates and industrial demands, particularly in PLC- and HMI-based automation systems.